ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMEN DALAM PENGAMBILAN KEPUTUSAN PEMBELIAN PRODUK MIE INSTAN MEREK SEDAAP - Guntur Suryo Putro (Jurnal Bisnis dan Kewirausahaan, 2017)
This study aims to analyze the factors that influence consumers in making purchasing decision of instant noodle brand product, to know the influence of independent variable to dependent variable used multiple linier regression analysis formula. The results of this study indicate that the variables of cultural, social, personal and psychological factors simultaneously have significant (significant) influence on the decision of Sedaap brand instant noodle product purchase. Psychological variables have a dominant influence on the purchase decision of instant noodle product of Sedaap brand.